A perspective on photonic multiprotocol label switching. - Murata, M.
Various MPLS-based IP over WDM integration techniques are considered in this article. In particular, this includes the circuit-switching MPλS framework for providing logical IP-layer topologies over optical lightpath routing networks. Additionally, an optical code label switching technique for photonic packet switching and its application to MPLS is also introduced, termed OC-MPLS. The related advantages and challenges of both of these approaches are discussed, and various future research issues are addressed
Keywords: MPLS-based IP over WDM integration techniques; OC-MPLS.; Logical IP-layer topologies; Optical code label switching technique; Optical lightpath routing networks; Photonic multiprotocol label switching; Photonic packet switching; Circuit-switching MPλS framework